Study of oleic acid as a surface modifying agent for oxide nanoparticles. (2022) - Singh, Anoop Pratap; Dwivedi, Ravi Kumar; Kumar, Rajan; Agarwal, Anupma; Suhane, Amit
Abstract: The development of nano lubricants has increased rapidly in recent years. With the addition of nano-additives to conventional oils to enhance tribological properties, the stability of nanoparticles remains a challenge, which can be ruled out with the help of surface modification of nanoparticles. So, oxide nanoparticles (Al2 O3, CuO, and SiO2 ) are analyzed in this study. The morphology of the nanoparticles is analyzed with the aid of a high-resolution field-emission scanning-electron microscope (HR FESEM) and found to be nearly spherical. The surface modification process is done with the help of oleic acid (OA). The surface modification process parameters are thoroughly discussed. The Fourier transform infrared spectroscopy (FTIR) result shows prominent oleic acid capping on oxide nanoparticles.